Hypoxia‐induced downregulation of cyclooxygenase 2 leads to the loss of immunoprivilege of allogeneic mesenchymal stem cells. Issue 11 (22nd September 2020) - Sareen, Niketa; Abu‐El‐Rub, Ejlal; Ammar, Hania I.; Yan, Weiang; Sequiera, Glen Lester; ShamsEldeen, Asmaa M.; Moudgil, Meenal; Dhingra, Rimpy; Shokry, Heba S.; Rashed, Laila A.; Kirshenbaum, Lorrie A.; Dhingra, Sanjiv
Abstract: Allogeneic mesenchymal stem cells (MSCs) from young and healthy donors are reported to hold the potential to treat several immunological and degenerative disorders. However, recent data from animal studies and clinical trials demonstrate that immunogenicity and poor survival of transplanted MSCs impaired the efficacy of cells for regenerative applications. It is reported that initially immunoprivileged under in vitro conditions, MSCs are targeted by the host immune system after transplantation in the ischemic tissues in vivo. We performed in vitro (in MSCs) and in vivo (in the rat model of myocardial infarction [MI]) studies to elucidate the mechanisms responsible for the change in the immunophenotype of MSCs from immunoprivileged to immunogenic under ischemic conditions. We have recently reported that a soluble factor prostaglandin E2 (PGE2) preserves the immunoprivilege of allogeneic MSCs. In the current study, we found that PGE2 levels, which were elevated during normoxia, decreased in MSCs following exposure to hypoxia. Further, we found that proteasome‐mediated degradation of cyclooxygenase‐2 (COX2, rate‐limiting enzyme in PGE2 biosynthesis) in hypoxic MSCs is responsible for PGE2 decrease and loss of immunoprivilege of MSCs. While investigating the mechanisms of COX2 degradation in hypoxic MSCs, we found that in normoxic MSCs, COP9 signalosome subunit 5 (CSN5) binds to COX2 and prevents its degradation by the proteasome. However, exposure to hypoxia leads to a decrease in CSN5 levels and its binding to COX2, rendering COX2 protein susceptible to proteasome‐mediated degradation. This subsequently causes PGE2 downregulation and loss of immunoprivilege of MSCs. Maintaining COX2 levels in MSCs preserves immunoprivilege in vitro and improves the survival of transplanted MSCs in a rat model of MI. These data provide novel mechanistic evidence that PGE2 is downregulated in hypoxic MSCs which is responsible for the post‐transplantation rejection of allogeneic MSCs. Therefore, our data suggest that the new strategies that target CSN5‐COX2 signaling may improve survival and utility of transplanted allogeneic MSCs in the ischemic heart.